Dynamic Mechanical Properties, Internal Friction and Dilatometric Changes in Annealed and Quenched AISI 4130 Steel: The Interplay of Phase Composition and Temperature - Matlakhova , Lioudmila A.; Pessanha , Emanuel C.; Alves , Henrique; Palii , Natalia A.; Monteiro , Sergio N. (Current Innovations in Chemical and Materials Sciences Vol. 4, 2024)
This chapter focuses on the dynamic elastic moduli and damping behavior in AISI 4130, as a function of temperature, and to correlate their changes with phase stability in this alloy with different initial structures: stable (annealed) and metastable (quenched), as a result of heat treatment. Elastic moduli and elastic stiffness constants of crystals have primary importance in materials design and materials discovery. Elastic properties of materials, such as Yung’s modulus (Ed), shear modulus (Gd), damping (Q-1), and their changes with temperature are important for their applications in engineering. The material characterization was performed using confocal microscopy, XRD, SEM, HV, impulse excitation technique (IET), and dilatometry. A stable structure, composed of ferrite (BCC) and pearlite (\(\alpha\)-Fe + Fe3C), was obtained by annealing. The metastable Metastable structure of martensite (BCT) was obtained by quenching. The Ed, Gd, and Q-1 were measured by varying the temperature from RT to 900 °C. The values of Ed and Gd, at RT, were determined as 201.5 and 79.2 GPa (annealed) and 190.13 and 76.5 GPa (quenched), respectively. In the annealed steel, the values Ed and Gd decrease linearly on heating up to 650 °C, with thermal expansion. The abnormally anomalous changes have been observed for alloys with two different initial states. However, it should be emphasized that the phase composition of these alloys is identical until phase transformation occurs during austenitization. In the quenched steel, weak changes occurred in the dilatometric curve, Ed, Gd, and Q-1, in the range of 350-450 °C, which indicated decompositions of the martensitic phase. A sharp decrease in the moduli and high peak of Q-1 were observed for both samples around 650–900 °C, revealing low lattice elastic stability of the phases during transformations [\(alpha\)(BCC) + Fe3C This study, utilizing IET, outlines the first exploration of Ed, Gd, \(\mu\), and Q-1 in AISI 4130 steel during temperature increase, contributing valuable insights for engineering applications in high-temperature environments.